The Influence of E-Modules and Demonstrations on School Children's Internet Addiction - Wardany, Nadia Sintia; Amalia, Linda; Sumartini, Sri; Suparto, Tirta Adikusuma; Puspita, Asih Purwandari Wahyoe; Dharmansyah, Dhika (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT The digital era has brought significant changes in the way children interact with technology, especially the internet. This community service (PkM) aims to explore the influence of e-modules and demonstrations as intervention strategies to combat internet addiction in school children. The activity was carried out at SDIT Plenary Cimahi City. This study was carried out by providing education to 57 students. The results of PkM activities showed that 47.4% of children had signs of internet addiction before being given intervention. Post-intervention results showed a significant reduction in the addiction rate to 36.8%. Health promotion sessions provided insight into the definition, contributing factors, symptoms, and preventive measures associated with internet addiction, highlighting the importance of parental involvement and social support. These findings underscore the effectiveness of structured educational interventions in reducing internet addiction among children, emphasizing the important role of community engagement in addressing this increasing problem in the digital era. Suggestions for further community service, it is hoped that the interventions provided can have an impact at the behavioral level. Keywords: Internet Addiction, School Children, E-Module, Demonstration